Incidence of Antibiotic Resistant Bacteria In Fish Sold In Local Market In Dhaka City - Das, KK; Sultana, R; Akter, F; Siddiqui, TA; Feroz, F (Stamford Journal of Microbiology, 2023)
Present study was designed to evaluate the microbial contamination in fish (Olive Barb, Bele, Pale-Carplet, Pabo Catfish, Olive, Tangra, Gizzard, Nola, Tatkini, Corica Soborna) samples were collected from the several local market of Dhaka city, Bangladesh. Most of the fish samples were found to be contaminated with huge number of micro-biota within the range of 105 to 106 CFU/g. The maximum total viable bacterial (TVB) load was estimated observed in Pale Carplet (Amblypharyngodon mola) (4.8×106 CFU/g) and the lowest count was found (1.5×105 CFU/g) in tangra (Mystus spp.) Escherichia coli and Klebsiella spp. were present in olive barb, bele, tangra and gizzard while Salmonella spp. and Vibrio spp. were present in olive barb, bele, tangra and gizzard fish samples. Moreover, most of the isolated bacteria exhibited resistance against maximum antibiotics like trimethoprime/sulfamethoxazole (25 μg), erythromycin (15 μg), amoxicillin (30 μg), Ceftriaxon (30 μg), ciprofloxacin (5 μg), streptomycin (10 μg), Ampicillin (10 μg). Microbial contamination in the fish samples especially those were resistant to drugs may pose a serious threat to public health. Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 38-41